Desarrollo de un modelo para la aplicación del alineamiento De las redes de valor de los productos fabricados en PET en Bogotá, Colombia (2017)
Through the research developed we looked to bring solution to the problem by what crosses the sector of articles manufactured from PET in the city of Bogotá, from the design of a logistic model that allows the participants of the industry align their activities and increase the perceived benefits to each and every one of them.